1996
DOI: 10.2351/1.4745427
|View full text |Cite
|
Sign up to set email alerts
|

Laser drilling of advanced materials: Effects of peak power, pulse format, and wavelength

Abstract: The quality of laser-drilled holes is significantly influenced by the laser peak power, pulse format, and wavelength. Three advanced materials are used to demonstrate the importance of choosing the correct laser parameters for a specific material. The materials are: (1) intermetallic single crystal nickel aluminide (NiAl) alloy; (2) N5, a single crystal nickel-based superalloy; and (3) a silicon carbide (SiC) ceramic matrix composite (CMC). The laser peak power is varied in terms of the pulse duration and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…After 30 minutes of curing at 65°C, the CO 2 laser was used at low power (30% of maximum speed, 22% of maximum power) to micro-machine the interfaces in order to remove the poorly conducting elastomer layer formed during curing and thereby expose the nanoparticles on the surfaces that will contact the fluids. This did not affect the nickel particles, since the laser wavelength (10.6 μm) was too long to be absorbed by this metal [42]. The resistance of the resulting interface was as low as 30 throughout its entire length (4 mm).…”
Section: Heating First Layer Sensor's Top Layer Curingmentioning
confidence: 99%
“…After 30 minutes of curing at 65°C, the CO 2 laser was used at low power (30% of maximum speed, 22% of maximum power) to micro-machine the interfaces in order to remove the poorly conducting elastomer layer formed during curing and thereby expose the nanoparticles on the surfaces that will contact the fluids. This did not affect the nickel particles, since the laser wavelength (10.6 μm) was too long to be absorbed by this metal [42]. The resistance of the resulting interface was as low as 30 throughout its entire length (4 mm).…”
Section: Heating First Layer Sensor's Top Layer Curingmentioning
confidence: 99%
“…Similarly, from work investigating alternative routes to the laser ablation-deposition (LAD) of Al 2 O 3 and Ti:saphire using CO 2 and excimer radiation, Dyer et al [10] found that laser wavelength was a major influence in determining the likelihood of successful deposition. A study conducted by Chen et al [11] using Nd:YAG and excimer lasers found that the quality of laser drilled holes was significantly influenced by laser wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Previously the main fundamental differences resulting from wavelength variations of CO, CO 2 , Nd:YAG and excimer lasers for a number of materials processing applications have been detailed [1][2][3][4]. Likewise, such practical comparisons between these traditional materials processing lasers and the more contemporary high power diode laser (HPDL) are even fewer in number.…”
Section: Introductionmentioning
confidence: 99%